Structural Changes in Steel 12GBA During Warm Rolling and Resistance to Brittle Fracture at Negative Temperatures; Metal Science and Heat Treatment; Vol. 59, iss. 11-12 - Derevyagina L. S. Lyudmila Sergeevna; Korznikov A. V.; Surikova N. S.; Gordienko A. I. Antonina Ildarovna (2018, 2018)
Title screen